Optimal Quantization in Decentralized Detection by Maximizing the Average Entropy of the Sensors - Wahdan, Muath A.; Altınkaya, Mustafa Aziz; Altınkaya, Mustafa Aziz (Institute of Electrical and Electronics Engineers Inc., 2019)
In a wireless sensor network the sensor outputs are required to be quantized because of energy and bandwidth requirements. We propose such a distributed detection scheme for a point source which is based on Neyman-Pearson criterion where sensor outputs are quantized maximizing the average output entropy of the sensors under both hypotheses. The quantized local outputs are transmitted to a fusion center (FC) where they are used to make a global decision. The performance of the proposed maximum average entropy (MAE) method in quantizing sensor outputs was tested for binary, ternary and quarternary quantization. The effects of the channel from the sensors to the FC is also addressed by simplified channel models. The simulation studies show the success of the MAE method.
27th Signal Processing and Communications Applications Conference (SIU) -- APR 24-26, 2019 -- Sivas Cumhuriyet Univ, Sivas, Türkiye
Keywords: Decentralized detection; Quantization; Point source; Field source; Wireless sensor networks (WSNs)